Algorithm of Protein Sequence Determination by Combination of the Edman Degradation Method and Shotgun Mass Spectrometry - Skvortsov, V.S.; Mikurova, A.V.; Vavilov, N.E.; Zgoda, V.G. (Biomedical Chemistry: Research and Methods, 2018)
An algorithm combining advantages of the Edman degradation method and de novo mass-spectrometric sequencing was developed. The protein from the “Diaskintest” diagnostic test was used for analysis. The protein was digested with trypsin and 5 steps of Edman degradation were carried out sequentially for the mixture of peptides. At each stage, the resulting mixture was analyzed by shotgun mass spectrometry analysis. The results of mass-spectrometry were analyzed both by the well-known de novo sequencing programs Novor and PepNovo+, and by own program that clustered individual spectra with a C-terminal signature formed by Y-ions. This approach allows us to determine confidently the amino acid sequence of the N-terminal part of the peptides obtained after the protein hydrolysis by trypsin.